Cetacean evoked potential audiometry by stranding networks enables more rapid accumulation of hearing information in stranded odontocetes - Houser, D.; Moore, K.; Sharp, S.; Hoppe, J.; Finneran, J. (J. Cetacean Res. Manage., 2023)
Knowing the hearing range and sensitivity of a marine mammal is fundamental to determining its potential for being impacted by ocean noise. Enabling stranding responders to perform hearing tests on stranded odontocetes is the most likely means by which most odontocete species will be tested and by which population-level variability in hearing will be determined. A portable auditory evoked potential (AEP) system was modified for use by stranding response teams and optimised to test odontocete hearing. Stranding responders were trained on the system and deployed it to strandings from 2010–2013. Eighteen partial or complete audiograms from common dolphins (n = 15) and Atlantic white-sided dolphins (n = 3) were obtained. Both species demonstrated typically delphinid audiograms with upper frequency limits of hearing between 113–160kHz; however, the region of best sensitivity in the Atlantic white-sided dolphin (28–56kHz) was 18–28 dB less sensitive than that of the common dolphin. A single common dolphin presented with severe hearing loss consistent with presbycusis in delphinids, but with undefined etiology. The number of audiograms obtained during the study greatly increases our knowledge about hearing in these species, neither of which are common to managed care facilities. In the case of the common dolphin, the number of animals tested allows a first estimate of population-level variability. Continued use of AEP systems by stranding responders will expedite the collection of audiometric information for previously untested species and permit sufficient sample sizes to determine population-level variability in the hearing of tested species.